A novel biomarker of chronic allograft dysfunction in renal transplant recipients (serum calreticulin and CD47) - Rasha Ibrahim Abdel Razek Gawish; Hayam Abdel Meguid El Aggan; Sabah Abdel Hady Mahmoud; Sara Ahmed Mohamed Mortada (The Egyptian Journal of Internal Medicine, 2020)
Abstract Background Chronic allograft dysfunction (CAD) is considered the leading cause of late allograft loss. The cluster of differentiation 47 (CD47) and calreticulin (CRT) are involved in many and diverse cellular processes. The present study was designed to study the role of the pro-phagocytic CRT and anti-phagocytic CD47 signals in patients with renal transplantation in relation to graft function. Thirty renal transplantation recipients (RTR) for more than 6 months [15 with stable renal function and 15 with chronic allograft dysfunction (CAD)] and 15 healthy controls were enrolled in the study. Quantification of CRT, CD47, and high-sensitivity C-reactive protein (hsCRP) levels in serum was done using standardized enzyme-linked immunosorbent assay (ELISA) kits. Measurement of renal function and urinary alkaline phosphatase (U.ALP) was done. Renal interstitial fibrosis (IF) was graded in renal biopsies of CAD. Results Serum CRT and urinary ALP levels were statistically significant higher (P < 0.001) while serum CD47 level was statistically significant lower (P < 0.001) in patients with CAD than patients with stable graft function and controls. There was statistically insignificant difference between controls and patients with stable graft function. Serum CRT and serum CD47 levels were positively correlated with each other and with worsening renal and tubular function, serum hsCRP in RTR and with degree of renal IF in patients with CAD (P < 0.05). Conclusions The activation and dysregulation of CRT and CD47 could play a role in the development of CAD and could be a potential biomarker for renal allograft dysfunction.